Analisis Pengaruh Rotasi Audit Dan Kepatuhan Pengelolaan Daerah Terhadap Kualitas Audit Di Inspektorat Kabupaten Luwu - Monalisa Monalisa; Nispa Sari; Sahrir Sahrir (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The change of auditors (audit rotation) and compliance in regional management are determinants that influence audit quality in the government sector. This study aims to evaluate the impact of audit rotation and the level of compliance in regional management on audit quality at the Inspectorate of Luwu Regency. This research adopts a quantitative approach by applying multiple regression analysis. Data were obtained through questionnaires distributed to 45 auditors at the Inspectorate of Luwu Regency. The findings reveal that audit rotation has a positive effect on audit quality, indicating that the change of auditors contributes to enhancing independence and objectivity in the financial audit process. Additionally, compliance with regional management also has a positive impact on audit quality, signifying that transparency and adherence to applicable regulations play a role in strengthening the effectiveness of regional financial oversight. Thus, this study concludes that audit rotation policies and compliance in regional management simultaneously contribute to improving audit quality in the government environment.